Future of human Chlamydia vaccine: potential of self-adjuvanting biodegradable nanoparticles as safe vaccine delivery vehicles. (4th March 2018) - Sahu, Rajnish; Verma, Richa; Dixit, Saurabh; Igietseme, Joseph U.; Black, Carolyn M; Duncan, Skyla; Singh, Shree R; Dennis, Vida A
ABSTRACT: Introduction : There is a persisting global burden and considerable public health challenge by the plethora of ocular, genital and respiratory diseases caused by members of the Gram-negative bacteria of the genus Chlamydia . The major diseases are conjunctivitis and blinding trachoma, non-gonococcal urethritis, cervicitis, pelvic inflammatory disease, ectopic pregnancy, tubal factor infertility, and interstitial pneumonia. The failures in screening and other prevention programs led to the current medical opinion that an efficacious prophylactic vaccine is the best approach to protect humans from chlamydial infections. Unfortunately, there is no human Chlamydia vaccine despite successful veterinary vaccines. A major challenge has been the effective delivery of vaccine antigens to induce safe and effective immune effectors to confer long-term protective immunity. The dawn of the era of biodegradable polymeric nanoparticles and the adjuvanted derivatives may accelerate the realization of the dream of human vaccine in the foreseeable future. Areas covered : This review focuses on the current status of human chlamydial vaccine research, specifically the potential of biodegradable polymeric nanovaccines to provide efficacious Chlamydia vaccines in the near future. Expert commentary : The safety of biodegradable polymeric nanoparticles-based experimental vaccines with or without adjuvants and the array of available chlamydial vaccine candidates would suggest that clinical trials in humans may be imminent. Also, the promising results from vaccine testing in animal models could lead to human vaccines against trachoma and reproductive diseases simultaneously.